Perancangan Sistem It Inventory Dengan Integrasi Ceisa Bea Cukai Berbasis ERP Pada PT. Topjaya Antariksa Electronics - Amelia Rahma Dewi; Samsoni (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Bonded Logistic Center is a business to make export and import transcation but the definition of Bonded Logistic Center is “A Bonded Piling Place for storing goods originating outside the customs area and/or goods originating from other places within the customs area, may be accompanied by 1 (one) or more simple activities within a certain period of time to be re-issued.” To make a transcation in Bonded Logistic Center the holding of business should have an IT Inventory System that can be checked in real time by the responsible Directorate General of Customs and Excise. According to Directorate General of Customs and Excise law No. PER-09/BC/2014 about "the application of a computer-based inventory information system for companies that use exemption, return, and bonded storage facilities, as well as data and/or information confidentiality by the directorate general of customs and excise." As the law said so PT. Topjaya Antariksa Electronics should have an IT Inventory System. In this research I made the system with odoo framework V12 Community, postgresql database. The conclusion of this research is IT Inventory System PT. Topjaya Antariksa Electronics have made with odoo framework V12 Community with postgresql that have one custom module so the responsible of directorate general of customs and excise can check the transaction and report in real time.